Perilaku Sehat Ibu Hamil dan Kematian Bayi: Perspektif Sosiologi Kesehatan - Sulyana Dadan; Nanang Martono; Urip Tri Wijayanti (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Infant mortality is one of the important indicators for assessing the degree of health and quality of life of residents in a region. Several studies that discuss the causes of infant mortality, highlight more external factors of pregnant women, such as social background, economy and availability of health services. Therefore, this study aims to examine the internal factors of pregnant women, namely the healthy behavior of pregnant women in relation to the emergence of cases of infant death. The research method used is descriptive quantitative by analyzing secondary of SDKI data 2017 in Central Java . Data is processed using descriptive statistics in the form of frequency distribution and cross tables. Referring to the concepts of health behaviors in a sociological perspective, this study found that the meaning of pregnant women to the concept of pregnancy also determines their behavior in undergoing the process of pregnancy towards the delivery process. This study concluded that healthy behavior of pregnant women such as pregnancy examination, drug consumption and postnatal examination of babies is one of the causes of infant mortality in Central Java province.